Nursing safety attitudes: relationship with time of experience and intention to leave the job - Gisele Hespanhol Dorigan; Damaris Ferreira Piffer Mingato; Edinêis de Brito Guirardello (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To evaluate the safety attitudes of the nursing staff and their relationship with staff adequacy and material resources, time of experience and intention to leave the job. Method: A descriptive and cross-sectional study in a teaching hospital, sampled by convenience, with the application of the Safety Attitudes Questionnaire, collected from January to April 2016. Results: 262 professionals participated, of whom 98 were nurses and 164 technicians. They reported a positive safety attitude for job satisfaction. The adequacy of staff and material resources positively influenced safety attitudes. There was a negative correlation between time of experience and perception of management, safety climate, working conditions and safe behaviors and, between the intention to leave the job and the teamwork climate, job satisfaction, and safe behaviors. Conclusion: The negative perception of safety attitudes was related to the time of experience and to the intention to leave the job.